Neonatal Mimicry of Caregivers at Home: Feasibility of an Asynchronous Online Paradigm. - Casey, Katherine; Neree, Benazir; Larrauri, Camila; Zeng, Guangyu; Ashton, Kira; Gill, Jeff; Simpson, Elizabeth A.; Bayet, Laurie (Infancy, 2026)
While early life sets the stage for later learning, comparatively less is known about newborns' cognition than that of older infants. A striking example is the lack of consensus regarding the extent to which newborns spontaneously mimic gestures, and whether such behavior drives bonding and learning. Despite the theoretical importance of these questions, practical challenges limit researchers' ability to engage newborns in behavioral research. Webcam‐based, asynchronous online studies have expanded developmental science's capacity to reach older infants. However, such scalable and replicable methods have yet to be deployed with younger infants. Taking a commonly‐used neonatal mimicry paradigm as a test case, we assessed the feasibility of leveraging an open‐source online platform (Children Helping Science) for asynchronous research with 0–6‐week‐olds and their caregivers. Caregivers modeled face movements to their 4–45 days‐old infants (N = 29, N = 17 included) while webcams filmed their infants' responses; 13 dyads participated more than once (72 included test videos). Preliminary evidence suggested that infants do not mimic caregivers' tongue protrusions (Bayes Factor ∼ ⅓). Data on the mimicry of caregivers' mouth openings was inconclusive (⅓ < BF < 3). Additional analyses identified a target sample size for future studies. Finally, we asked whether caregivers perceived their newborns' behavior as imitative. Caregivers' perceptions of mimicry reflected infants' behaviors but did not align with an often‐used metric of mimicry ("imitators"). These results demonstrate the feasibility of asynchronous online behavioral studies with newborns and provide a foundation for future research on neonatal mimicry of caregivers.